Instrument Referral Criteria for PlusoptiX, SPOT and 2WIN Targeting 2021 AAPOS Guidelines [Corrigendum] - Arnold R; Silbert D; Modjesky H (Clinical Ophthalmology)
Arnold R, Silbert D, Modjesky H. Clin Ophthalmol. 2022;16:489—505. The authors have advised that Table 3 on page 497 is incorrect. In the SPOT section, <4y, sensitive row, Cylinder column, the value should be ≥2.75 instead of 3.75. The correct Table 3 is as follows.